THE USE OF SOCIAL MEDIA AS AN EFFECTIVE LEARNING MEDIUM DURING THE COVID-19 PANDEMIC - Sri Hapsari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This exploratory article was concerned with the use of social media platforms as learning media during the covid-19 pandemic. Indonesia government issued a policy to work at home, study at home, and worship at home during the pandemic. Several social media platforms became popular among Indonesians during the pandemic. This study explored a concept, which meant understanding the developing phenomena in order to gain insights used for further research. Respondents were four students who attended lectures on organizational behaviour. The data were collected through observation, assignment, and unstructured interviews. The findings showed the diversity of social media chosen by students with various considerations such as the amount of internet quota, trends in social media applications, and creativity development, as well as several things that need to be considered by lecturers and students in online learning.